Clinicoepidemiological Study of Cutaneous Leishmaniasis: A Hospital Based Study - Pradhan, Sushmita; Shrestha, Shristee; Khadka, Damber; Parajuli, Niraj; Baral, Suwash; Tsuruta, Daisuke (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: Cutaneous leishmaniasis is a tropical disease transmitted by the bite of an intracellular parasite infected sandfly. Visceral leishmaniasis is common in Nepal. However, cutaneous leishmaniasis remains rare with only limited number of cases documented in Nepal. Objectives: To describe the clinical and epidemiological distribution of cutaneous leishmaniasis in Karnali province of Nepal. Materials and Methods: All cases clinically diagnosed from direct microscopic Giemsa-stain smears, histopathology or fine needle aspiration cytology as cutaneous leishmaniasis were enrolled in the study for one year. Demographic data and clinical details were recorded on a printed proforma. Statistical analysis was done using STATA/SE version 15.0 for MacBook. Results: Only 46 cases with age ranging from 2 to 75 years were included in the study. Mean age was 23±2.45 years. Majority of cases below 20 years (47.83%) were infected. Male to female ratio was 0.70:1. Mean duration of the disease was 4.96±0.47 months. Single lesions (73.91%) were mostly present. Single lesions were particularly presented on the face (73.53%). Cutaneous leishmaniasis (95.65%) outnumbered mucocutaneous one on lips (4.35%). Ulcerative-papulonodular type lesions (58.70%) were mostly presented in the cases. Kalikot district (56.52%) had the majority of cutaneous leishmaniasis cases in Karnali province. Majority of the cases presented during the months of February, March, April, August, November, and December (65.22%). Conclusion: The study concluded that the increase in cutaneous leishmaniasis is alarming in the Kalikot district of Karnali province in Nepal. The result of this study would continue contributing to the existing data in the literature and encourage early diagnosis and treatment of cutaneous leishmaniasis.